2014
DOI: 10.1016/j.jpeds.2014.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Cat and Dog Exposure and Respiratory Morbidities in Cystic Fibrosis

Abstract: Objective To understand the triggers that may impact respiratory health in cystic fibrosis (CF), including the effects of pets, because environmental factors contribute to one-half of the variation in lung function in patients with CF. Study design A total of 703 subjects with CF were recruited through the U.S. CF Twin-Sibling Study. Questionnaires were used to determine the presence/absence of cats and dogs in households with a child with CF. Questionnaires, chart review, and U.S. CF Foundation Patient Regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 25 publications
0
16
1
Order By: Relevance
“…The worst progression of all lung function parameters was found in patients with ABPA even surpassing the effect of chronic P. aeruginosa infection (p < 0.0001). Interestingly, ABPA was not found as a factor being associated with dog or cat exposure in a recent multicenter sibling CF study . An explanation for this could be that the CF population analyzed there was younger (mean age 11.8 ± 8.8) than the CF population in this study (mean age 25.4 ± 13.2).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…The worst progression of all lung function parameters was found in patients with ABPA even surpassing the effect of chronic P. aeruginosa infection (p < 0.0001). Interestingly, ABPA was not found as a factor being associated with dog or cat exposure in a recent multicenter sibling CF study . An explanation for this could be that the CF population analyzed there was younger (mean age 11.8 ± 8.8) than the CF population in this study (mean age 25.4 ± 13.2).…”
Section: Discussioncontrasting
confidence: 62%
“…Recent data indicate that pet ownership is an environmental factor influencing the health of patients with CF. This includes case reports on pathogen transmission from pet to patients with CF and vice versa and a multicenter sibling study on the association of pet ownership with infection outcomes in these patients . Previous results from our group confirm transmission of various pathogens between pet and patients with CF, among them A. fumigatus .…”
Section: Discussionmentioning
confidence: 53%
“…Although studies have focused on bronchial hyper‐responsiveness (BHR) or specific airway resistance (sRaw) assessed by challenge tests, few have specifically focused on FEV 1 , FVC, and their ratio along with PEF. Most of these studies, including cross‐sectional and birth cohort study designs, found no associations for living with pets and the risk of respiratory or allergic conditions . However, in a cohort study, Bertelsen et al .…”
Section: Introductionmentioning
confidence: 99%
“…Case reports describe interspecies transmission of bacteria between cats/dogs and CF patients (Ner et al, 2003;Mohan et al, 2008;Register et al, 2012). Morrow et al investigated cat and dog exposure in 703 CF patients (Morrow et al, 2014): 47.2% reported dog, and 28.1% reported cat ownership (Morrow et al, 2014). Combined cat-dog ownership was associated with wheezing, but no differences in lung function, self-reported environmental allergies, or ABPA were reported (Morrow et al, 2014).…”
Section: Discussionmentioning
confidence: 99%